Eksklusi Elektoral dalam Sistem Multipartai Indonesia: Dampak Parliamentary Threshold terhadap Partai Non-Parlemen pada Pemilu 2024 - Siti Afra Aafiyah; Gendis Dewantari; Nasytha Muthiah; Nazwa Namira Putri Rusdiandi; Vallerian Antaresa; Restu Rahmawati (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
In Indonesia’s multi-party democratic system, the implementation of a 4% parliamentary threshold is intended to simplify the party system and strengthen the stability of the presidential government. However, this policy also raises issues of political representation because not all voters’ votes can be converted into parliamentary seats. This study aims to analyze the impact of the parliamentary threshold on the electoral exclusion of non-parliamentary parties and its implications for the quality of representative democracy in the 2024 General Election. The research employs a qualitative method with a library research approach through the analysis of academic literature, legal regulations, and official data from the 2024 Election. The findings indicate that the parliamentary threshold creates disproportionality between vote acquisition and the distribution of seats in the House of Representatives, causing millions of votes to become wasted votes without political representation. This policy strengthens the dominance of major parties, limits the competitive space for small and new parties, and reduces the level of democratic inclusiveness in Indonesia. Therefore, an evaluation of the parliamentary threshold policy is necessary to create a balance between governmental effectiveness and fair political representation.